In silico comparative genomic analysis unravels a new candidate protein arsenal specifically associated with Fusarium oxysporum f. sp. albedinis pathogenesis - Hafida Ayada; Boutayna Dhioui; Hamid Mazouz; Abdelhay El harrak; Fatima Jaiti; Bouchra Ouhmidou; Mohammed Diouri; Mohieddine Moumni (Scientific Reports)
Abstract Fusarium oxysporum f. sp albedinis (Foa) is a devastating fungus of date palms. To unravel the genetic characteristics associated with its pathogenesis, the two available genomes of Foa 133 and Foa 9 were compared with 49 genomes of 29 other pathogenic formae speciales belonging to Fusarium oxysporum species complex (FOSC). Foa 133 and Foa 9 have genomes of 56.23 Mb and 65.56 Mb with 17460 and 19514 putative coding genes. Of these genes, 30% lack functional annotation with no similarity to characterized proteins. The remaining genes were involved in pathways essential to the fungi's life and their adaptation. Foa secretome analysis revealed that both Foa strains possess an expanded number of secreted effectors (3003 in Foa 133 and 2418 in Foa 9). Those include effectors encoded by Foa unique genes that are involved in Foa penetration (Egh16-like family), host defense mechanisms suppression (lysM family) and pathogen protection (cysteine-rich protein family). The accessory protein SIX6, which induces plant cell death, was also predicted in Foa. Further analysis of secreted CAZymes revealed an arsenal of enzymes involved in plant cell wall degradation. This arsenal includes an exclusively Foa-specific CAZyme (GH5-7). Transcription factors and membrane transporters (MFS) involved in fungicide efflux have been predicted in Foa, in addition to a variety of secondary metabolites. These comprise mycotoxins as well as chrysogin, the latter provides Foa with resistance against adverse environmental conditions. Our results revealed new Foa proteins that could be targeted in future research in order to manage Bayoud disease.